Perlindungan HAM dalam Kasus Kekerasan Seksual di Pondok Pesantren - Lia Sulistiarini; Nelsi Mersa Dila; Fitria Rahmadina; Nurzelika Putri; Septia Tri Wahyuni; Darma Wita; Oktarina Berlianti; Deffny Gusmalinda; Mila Wilanda; Hambali Hambali (Pusat Riset dan Inovasi Nasional, 2024)
In this article, sexual violence in Islamic boarding schools is discussed in relation to human rights violations. Many incidents show the practice of sexual violence involving officials, even though Islamic boarding schools are considered educational institutions that instill moral and religious values. The purpose of this study is to determine the types of human rights violations, the factors that cause sexual violence, and the function of Islamic boarding schools in preventing and implementing efforts to protect victims. This study uses a qualitative method using case studies and literature analysis. The results of the study indicate that verbal, physical, and psychological violence are forms of sexual violence in Islamic boarding schools. These incidents are influenced by patriarchal cultural norms, unequal power dynamics, and lack of supervision from outside parties. Victims suffer greatly from the impact, both intellectually and mentally. Therefore, to provide a safe and free learning environment from sexual violence, a comprehensive strategy is needed that involves the rule of law, increasing awareness of human rights, and providing psychosocial support to victims.